2003
DOI: 10.1249/01.mss.0000069755.40046.96
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Remodeling after Spinal Cord Injury

Abstract: In summary, femoral artery diameter and maximal hyperemic blood flow response per unit muscle volume are not different between SCI and AB individuals. Vascular atrophy after SCI appears to be closely linked to muscle atrophy. Furthermore, the SCI compared with AB individuals had a prolonged time to recovery, which may suggest decreased vessel reactivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
91
2
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(99 citation statements)
references
References 28 publications
5
91
2
1
Order By: Relevance
“…22 The results of this study do not support this relationship since electrical stimulation training resulted in an increase in muscle size with no change in either of these parameters. Previous studies have reported that electrical stimulation training increases arterial diameter.…”
Section: Discussioncontrasting
confidence: 60%
See 2 more Smart Citations
“…22 The results of this study do not support this relationship since electrical stimulation training resulted in an increase in muscle size with no change in either of these parameters. Previous studies have reported that electrical stimulation training increases arterial diameter.…”
Section: Discussioncontrasting
confidence: 60%
“…37 Individuals with SCI have reduced reactive hyperemic blood flow in comparison to AB controls 22 and training has been found to improve on this deficit by 78%. 33 In this study, reactive hyperemia did not appear to change throughout the training intervention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Olive et al 15 reported impaired or altered BF to affected muscles in SCI patients during exercise or ES-induced contractions that may have contributed to increased muscle fatigue. [15][16][17] Crespo Ruiz et al 13 described the physiological training effects: muscles will enlarge and become stronger and circulation will improve.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17] Crespo Ruiz et al 13 described the physiological training effects: muscles will enlarge and become stronger and circulation will improve. ES-induced muscle activation with tetanic contractions allows mechanically unrestricted BF and may lead to less fatigue as a result of changes in tissue.…”
Section: Discussionmentioning
confidence: 99%